Cytoprotective Effects of Dinitrosyl Iron Complexes on Viability of Human Fibroblasts and Cardiomyocytes - Akentieva, Natalia Pavlovna; Sanina, Natalia Alekseevna; Gizatullin, Artur Rasimovich; Shkondina, Natalia Ivanovna; Prikhodchenko, Tatyana Romanovna; Shram, Stanislav Ivanovich; Zhelev, Nikolai; Aldoshin, Sergei Michailovich (Frontiers in Pharmacology, 2019)
Nitric oxide (NO) is a significant signalling molecule, which plays a pivotal role in maintaining vascular homeostasis. Dinitrosyl iron complexes (DNICs, donors NO) are widely used in the treatment of cardiovascular disease. However, the role of DNICs in metabolic processes of cell, their protective properties in doxorubicin-induced toxicity remain to be clarified. Here, we found that novel class of mononuclear DNICs with functional sulfur-containing ligands enhanced the cell viability of human lung fibroblasts and cardiomyocytes. Moreover, DNICS demonstrated remarkable protection against doxorubicin-induced toxicity in fibroblasts and in H9c2 cells. Data revealed that the DNICs compounds modulate the mitochondria function by decreasing the mitochondrial membrane potential (ΔΨm). Results of flow cytometry showed that DNICs were not affected the proliferation, growth of fibroblasts. Moreover, this study revealed that DNICs were not affected on the level of glutathione and reactive oxygen species in cells. In addition the results indicated that DNICs maintained the ATP equilibrium in cells. Taken together, these findings show that DNICs have protective properties in vitro. It was further suggested that DNICs may be uncouplers of oxidative phosphorylation in mitochondria and protective mechanism is mainly provided by the leakage of excess charge through the mitochondrial membrane. It is assumed that the DNICs have the therapeutic potential for treating cardiovascular diseases and for decreasing of chemotherapy-induced cardiotoxicity in cancer survivors.